Perhitungan Tebal Perkerasan Ruas Jalan Taeno-Wakal, Ambon Maluku - Rumbara, Isdam; Tuasuun, Septo Christoffel; Matitaputty, Apri Adam (JURNAL ILMIAH NUSANTARA, 2025)
Roads as one of the transportation infrastructures that play an important role in people's lives in increasing economic activities in a place because they help people to go or send goods faster to their destinations. With the construction of this road, it is expected to increase and accelerate the distribution of agricultural products, plantations and basic needs of the surrounding community. Road pavement is a layered structure located above the base soil, there is a top foundation layer and a bottom foundation layer, each layer consisting of compacted aggregates that function to channel stress due to wheel loads. There are 3 types of road pavement, asphalt or flexible pavement, composite (Composite pavemet) and concrete/rigid pavement. In determining the thickness of flexible pavement, there are several methods to use, including in this study using the component method and the MDP 2017 method. The location of this research is located in Taeno, Ruma Tiga Village, Teluk Ambon District, Maluku Province, along 3.075 km, with a road width of 5 meters. The results of the 2017 MDP method pavement layers for new road pavements were obtained for the AC-WC surface layer, which was 4.5 cm, the Class A aggregate top base layer was 40 cm, and the selected embankment bottom base layer was 10 cm.Keywords: road pavement, Transportation, component method, MDP 2017.